1981
DOI: 10.1093/bja/53.10.1049
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Org Nc45 (Norcuron) in Patients With and Without Renal Failure

Abstract: To determine the influence of renal failure on the pharmacokinetics and neuromuscular blockade of Org NC 45 (Norcuron), a new monoquaternary homologue of pancuronium, 13 patients under halothane and nitrous oxide anesthesia were studied. Org NC 45 was administered by 2-min infusion in doses of 0.28 mg kg-1 (normal renal function group, n = 4) and 0.14 mg kg-1 (renal failure group, n = 5). Four additional patients with normal renal function were given Org NC 45 0.14 mg kg-1 to determine the onset, duration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…S In man, renal failure is associated with only small increases in the duration of neuromuscular block and recovery rate 6 as a result of statislically insignificant alterations in the pharmacokinetic behaviour of vecuronium in renal failure. 7 However, these observations are based upon small patient populations and there is no information of the potency, cumulative tendency, or reversibility of vecuronium in renal failure in man.…”
mentioning
confidence: 99%
“…S In man, renal failure is associated with only small increases in the duration of neuromuscular block and recovery rate 6 as a result of statislically insignificant alterations in the pharmacokinetic behaviour of vecuronium in renal failure. 7 However, these observations are based upon small patient populations and there is no information of the potency, cumulative tendency, or reversibility of vecuronium in renal failure in man.…”
mentioning
confidence: 99%
“…1 whereby an epidural catheter is inserted into the chest at thoracotomy to provide access to the pleural cavity for postoperative infusion of bupivacaine. He suggests that this technique offers an alternative to more established postthoracotomy analgesic methods such as epidural, parenteral narcotics or intercostal nerve blocks.…”
Section: Cricoid Pressurementioning
confidence: 99%
“…Vecuronium has also been described as a suitable non-depolarizing agent for the clinically or anatomically anephric patient. ~.2 Fahey et al 2 showed no difference in onset or recovery time of vecuronium between normal and cadaver transplant patients. Another group t found no difference in duration of block or evidence of accumulation after multiple doses of vecuronium were administered to normal and anepbric patients.…”
Section: Discussionmentioning
confidence: 96%
“…They found no difference between the two groups in duration of action of either drug and no evidence of accumulation. Fahey et al 2 compared the pharmacokinetics of vecuronium in patients with and without renal failure and found no significant difference in duration or evidence of accumulation between the two groups. Other authors 3'4 have demonstrated that atracurium showed no evidence of accumulation or prolongation of effect in the renal failure patient.…”
mentioning
confidence: 99%